GENESIS OF GENDER RELATIONS IN UKRAINIAN LANDS IN XIV - XVIII CENTURIES - Mykhaylyuk, Vitalii; Mykhaylyuk, OlenaLjwtyn (Sworld-Us Conference proceedings, 2023)
The study, analysis and generalization of the development of gender relations in the past history of our country are one of the aspects of scientific and theoretical research and practical needs in this area. This prompted the authors to consider the prob